KAJIAN EFISIENSI TEKNIS, ALOKATIF DAN EFISIENSI EKONOMI USAHATANI PADI SAWAH DALAM RANGKA PENINGKATAN PRODUKTIVITAS PADI DI KABUPATEN KERINCI PROVINSI JAMBI DENGAN PENDEKATAN STOCHASTIC FRONTIER - Nainggolan, Saidin; Wahyuni, Ira; Oktari Ulma, Riri (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
The purpose of this study (1) Analyze the effect of the use of inputs on rice production with the stochastic frontier production function model approach. (2) Analyzing the potential for increasing rice productivity through the study of technical efficiency, allocative efficiency and economic efficiency of rice farming in Kerinci Regency (3) Making reconstruction of optimal use of inputs in order to increase rice productivity so that technical efficiency, allocative efficiency and economic efficiency are beneficial for farmers. This research was conducted in Keliling Danau and Danau Kerinci Districts. Site selection is done purposively. The sample size was 80 farmers. The analytical method used to estimate technical efficiency, allocative, and economic efficiency with the stochastic frontier approach. The response of the amount of production to changes in the number of factors of production has a significant effect on farm efficiency. The low level of use of inputs and not optimal due to low farming technology causes low efficiency of lowland rice farming in Kerinci Regency both technical efficiency, allocative efficiency and economic efficiency are still relatively low. Increased farming efficiency is influenced by the performance of farmers in managing their farming and the use of farming technology in the use of certain inputs. Improved optimal efficiency can be done by using the optimal input of the estimation results. Keywords: Technical Efficiency, Allocative, Economy, Stochastic Frontier Analysis